Direct conversion of syngas into aromatics over a bifunctional catalyst: inhibiting net CO2 release. Issue 39 (9th April 2020) - Zhou, Wei; Zhou, Cheng; Yin, Haoren; Shi, Jiaqing; Zhang, Guoquan; Zheng, Xinlei; Min, Xiaojian; Zhang, Zhiqiang; Cheng, Kang; Kang, Jincan; Zhang, Qinghong; Wang, Ye
Abstract : Co-feeding of CO2 did not affect syngas conversion to aromatics but significantly suppressed CO2 formation over bifunctional ZnO–ZrO2 /H-ZSM-5 catalyst. Abstract : Tandem catalysis via methanol intermediate is a promising route for the direct conversion of syngas into aromatics. However, the simultaneous formation of CO2 is a serious problem. Here, we demonstrate that CO2 was formed by the water-gas shift (WGS) reaction (CO + H2 O → CO2 + H2 ) over a ZnO–ZrO2 /H-ZSM-5 catalyst, and the net CO2 formation could be inhibited without affecting the formation of aromatics by co-feeding CO2 .